Novel Cerium Phosphate–Citric Acid Nanocomposites for Biomedical Applications in Regenerative Medicine: In Vitro and In Vivo Study - Ekaterina V. Silina; Natalia E. Manturova; Elena L. Chuvilina; Akhmedali A. Gasanov; Olga I. Andreeva; Elena B. Artyushkova; Mikhail P. Gladchenko; Aleksandr V. Ivanov; Victor T. Dudka; Sergey Y. Mironov; Daria D. Tkachenko; Anatoly V. Skalny; et al. (International Journal of Molecular Sciences, 2026)
The aim of the study was to synthesize nanocomposites based on cerium orthophosphate stabilized with citrate at different ratios for biomedical applications, and to evaluate its safety in different animal species. Nanocomposites were synthesized using four different initial mass ratios of Ce(NO3)3 × 6H2O to citric acid: 1:5 (Ce:5CA), 1:3 (Ce:3CA), 1:1 (Ce:1CA), and 1:0.5 (Ce:0.5CA). The obtained products were characterized by a series of physicochemical methods including X-ray diffraction, transmission electron microscopy, and IR spectroscopy. Biomedical studies of the sols were performed to evaluate redox activity and their effects on the metabolism and proliferation of human fibroblasts. Safety studies were carried out in different animal species, including determination of the acute toxicity of the selected nanocomposite following application to intact skin and intragastric administration, as well as determination of subchronic toxicity using a model of acute experimental full-thickness skin wounds. According to the physicochemical studies, all synthesized nanocomposites contained nanocrystals with bimodal dimensions (width 3–10 nm, length 15–40 nm) and diffraction peaks characteristic of CePO4. IR spectroscopy demonstrated the formation of new chemical bonds. Antioxidant activity was observed for the Ce:3CA, Ce:1CA, and Ce:0.5CA samples, being most pronounced for Ce:1–0.5CA, whose antioxidant capacity exceeded that of ascorbic acid. In contrast, Ce:5CA exhibited pro-oxidant activity at all tested concentrations. Biocompatibility with human cells was demonstrated. Ce:0.5CA was identified as the most promising candidate for biomedical applications owing to its highest regenerative and antioxidant potential and its demonstrated safety in animals following topical and intragastric administration, as well as in wound models. Histomorphological examination of the internal organs supported the safety and potential of the developed nanocomposites for skin regeneration and wound healing.